Calming Your Anxious Mind : How Mindfulness and Compassion Can Free You from Anxiety, Fear, and Panic. - Brantley, Jeffrey (New Harbinger Publications, 2007)
This is a major revision of the classic book using mindfulness to overcome anxiety. It includes information on the latest research into mindfulness, new step-by-step exercises, and new thoughts on taking daily mindfulness to deeper and more rewarding levels.